Development of myiasis vaccine: In vitro detection of immunoprotective responses of peritrophic membrane protein, first instar larva Ll supernatant and pellet antigen of fly Chrysomyia bezziana in sheep - Sukarsih .; S Partoutomo; E Satria; C.H Eisemann; P Willadsen (Indonesian Center for Animal Research and Development (ICARD), 1999)
Myiasis control by means of individual treatment of animals which are mainly rised extensively is time consumed and expensive. The alternative way to control this disease by vaccination is considered effective and economically accepted. However the expected vaccine is now still being developed under a collaborative project between CSIRO, Inter-University Centre on Biotechnology-ITB and Research Institute for Veterinary Science and funded by ACIAR. There are several antigens have been identified as vaccine candidates and an in vitro bioassay technique has been developed for assessing the immunoresponses of vaccine in sheep. Three antigens were used for vaccines in this study, these included protein peritrophic membrane (PM), soluble extract (SE) and pellet extract (PE) of 1st instar larvae of Chrysomya bezziana. Twenty four experimental sheep were divided into 4 groups of 6 animals, 3 groups of animals were injected with PM, SE and PE vaccines with the dose rate of 0.5 g PM/head, 0.8 g PE/head and 4.2 ml LE/head respectively, and the other one group was injected with 4 ml PBS/head as a control group. Vaccination with the same dose was repeated 4 weeks after the 1st vaccination as a booster, and 2 weeks after the booster the sheep were challenged with live larvae, 3 days after challenge animals were killed. Sera were collected at the day of vaccination, 4 weeks after vaccination, 2 weeks after booster, and 3 days after challenge. An in vitro bioassay technique was conducted by culturing 1st instar larvae on five media containing sera collected from each experimental animal. The effects of sera on cultivated larvae were assessed by means of larval weight and larval mortality rate. The results indicated that the growth rate and survival of cultivated larvae in media containing anti-PM sera were significantly lower (P<0.01) compared to the larvae cultivated on media with sera on the day of vaccination. The larval weight depression by anti- PM sera collected at 3 days after challenge was 65% of that larvae cultivated on media with sera collected on the day of vaccination. Anti-PM sera depressed the growth rate and survival of larvae significantly greater (P<0.05) than that of anti-PE or anti-LE sera. It is concluded that PM has the best immunoresponses and as the candidate of choice for myiasis vaccine. Key words : In vitro bioassay, myiasis, immunoresponses, Chrysomya bezziana